Pemanfaatan Artificial Intelligence untuk Mendukung Tugas Guru di SMA Negeri 1 Bodeh - Pujiono, Imam Prayogo; Prayogi, Arditya; Shofiani, Rissa; Yuliyanti, Tsalisa; Iskarim, Mochamad (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2024)
The development of information and communication technology (ICT) in the era of the Industrial Revolution 4.0 has brought significant changes in various aspects of life, especially in education. One of the technologies that has gained attention in education is Artificial Intelligence (AI). In education, AI has great potential to revolutionize teaching and learning methods. AI can support tasks that humans previously could only do, such as creating teaching materials and evaluating learning. SMA Negeri 1 Bodeh is one educational institution committed to improving education quality through technology integration. However, based on initial observations, it was found that teachers' skills in utilizing AI technology to support teaching tasks were still limited. Therefore, a “Workshop on Utilisation of Artificial Intelligence to Support Teachers' Tasks at SMA Negeri 1 Bodeh” was held. In this workshop, teachers were given training on how to use AI platforms such as ChatGPT and Google Gemini to support teachers' tasks. This activity involved 28 teachers and used presentation, practicum, and discussion methods. The results of the workshop showed a significant improvement in teachers' skills in using AI, this can be seen from the results of the Pre-Test and Post-Test questionnaires, which showed an average increase of  12 teachers who previously stated that they could not, become able to use AI to support their duties as teachers, such as in creating teaching materials and exam questions. This increase shows that the workshop successfully achieved its goal of improving teachers' competence in utilizing AI to support their duties. The suggestion for the future is that the school is expected to provide support in the form of further training and support the use of AI on an ongoing basis.   Abstrak Perkembangan teknologi informasi dan komunikasi (TIK) pada era Revolusi Industri 4.0 telah membawa perubahan yang signifikan dalam berbagai aspek kehidupan, khususnya dalam bidang pendidikan. Salah satu teknologi yang mendapatkan perhatian dalam dunia pendidikan adalah Artificial Intelligence (AI). Dalam konteks pendidikan, AI memiliki potensi besar untuk merevolusi metode pengajaran dan pembelajaran. AI mampu mendukung tugas-tugas yang sebelumnya hanya bisa dilakukan manusia, seperti pembuatan materi ajar dan evaluasi pembelajaran. SMA Negeri 1 Bodeh, merupakan salah satu institusi pendidikan yang berkomitmen untuk meningkatkan kualitas pendidikan melalui integrasi teknologi. Namun, berdasarkan observasi awal, ditemukan bahwa keterampilan guru dalam memanfaatkan teknologi AI untuk mendukung tugas-tugas mengajar masih terbatas. Oleh karena itu diadakan “Workshop Pemanfaatan Artificial Intelligence untuk Mendukung Tugas Guru di SMA Negeri 1 Bodeh”, pada workshop ini para guru diberikan pelatihan untuk menggunakan platform AI seperti ChatGPT dan Google Gemini untuk mendukung tugas guru. Kegiatan ini melibatkan 28 guru dan menggunakan metode presentasi, praktikum, dan diskusi. Hasil workshop menunjukkan peningkatan signifikan dalam keterampilan guru menggunakan AI, hal ini terlihat dari hasil kuesioner Pre-Test dan Post-Test yang menunjukkan peningkatan rata-rata sebanyak 12 guru yang sebelumnya menyatakan tidak bisa, menjadi bisa menggunakan AI untuk mendukung tugas mereka sebagai guru, seperti dalam membuat materi ajar dan soal ujian. Peningkatan ini menunjukkan bahwa workshop berhasil mencapai tujuannya dalam meningkatkan kompetensi guru dalam memanfaatkan AI untuk mendukung tugas mereka. Saran untuk masa depan adalah pihak sekolah diharap dapat memberikan dukungan berupa pelatihan lanjutan dan mendukung penggunaan AI secara berkelanjutan.